PENERAPAN ADAB DAN AKHLAK DALAM BERKOMUNIKASI EFEKTIF PADA SISWA-SISWI PONDOK PESANTREN AL FIRDAUS BANDAR LAMPUNG - Muhammad Singgih (Al Mufid, 2021)
A child has enormous potential to develop. In the process, sometimes teachers without realizing it cannot communicate effectively with their students, this often happens, children do not respond to what the teacher says because the sentences are difficult for students to understand, the sentences spoken are convoluted and too long. The method of implementation before this service activity is carried out, first is a preliminary orientation. This orientation activity is carried out to get an idea of ​​the material needs. After we held training activities, it can be concluded that this activity is very beneficial for students, especially for students at the Al Firdaus Islamic Boarding School in Bandar Lampung. Teachers must have strategies in communicating with children who have different backgrounds. This can be seen when students interact with teachers who have shown good language, are polite, easy to understand by their students, and their students seem happy to interact with their teachers